The age of informed consent : a European history - Hostiuc, Sorin; Buda, Octavian, 1966- (Cambridge Scholars Publishing, 2018)
This volume analyses the conceptualization and the practical application of the concept of informed consent in various parts of continental Europe, and identifies whether informed consent can be seen as a clearly identifiable concept. The focus here is on the evolution of informed consent in France, Germany, Croatia, Turkey and Romania, with comparisons being made to the ""traditional"" history of the concept, mainly constructed in the US and the UK. The book will appeal to physicians, bio-ethicists and historians, as it provides the answers to some practical difficulties in applying informed